Pendidikan Qur’ani: Kajian Tafsir QS. Al-Qashash Ayat 77 terhadap Nilai dan Prinsip - Muhammad Hulaimi Hatami (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Education in Islam holds a central role in shaping the lives of individuals and society. However, challenges in Indonesia's education system, such as violations of ethical codes, school violence, and insufficient support for students with disabilities, highlight the need for a more holistic approach grounded in Qur’anic values. This study aims to examine the educational values and principles in Q.S. Al-Qashash: 77 and develop practical applications for contemporary education. Utilizing library research and a descriptive-analytical approach, the study identifies four key principles: Prioritization, which emphasizes the hereafter as the ultimate goal while utilizing the world as a means; Balance, maintaining harmony between worldly and spiritual matters; Excellence (Ihsan), encouraging goodness in all aspects of life; and Anti-Injustice, avoiding harm to the environment and society. These principles provide a foundation for integrating academic achievement with noble character development. The study recommends a Qur’anic-based educational approach that harmonizes spiritual and academic values to nurture a generation that excels intellectually, embodies virtuous character, and aims for both worldly success and eternal happiness.